Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the system of equations using substitution, follow these steps:
Given equations:
1. [tex]\( y = x - 4 \)[/tex]
2. [tex]\( 4x + y = 26 \)[/tex]
### Step 1: Substitute the expression for [tex]\( y \)[/tex] from the first equation into the second equation.
From the first equation, we can express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = x - 4 \][/tex]
Now, substitute [tex]\( y = x - 4 \)[/tex] into the second equation:
[tex]\[ 4x + (x - 4) = 26 \][/tex]
### Step 2: Simplify the equation and solve for [tex]\( x \)[/tex].
Combine like terms:
[tex]\[ 4x + x - 4 = 26 \][/tex]
[tex]\[ 5x - 4 = 26 \][/tex]
Add 4 to both sides of the equation:
[tex]\[ 5x = 30 \][/tex]
Divide both sides by 5:
[tex]\[ x = 6 \][/tex]
### Step 3: Solve for [tex]\( y \)[/tex] using the value of [tex]\( x \)[/tex].
Substitute [tex]\( x = 6 \)[/tex] back into the first equation:
[tex]\[ y = 6 - 4 \][/tex]
[tex]\[ y = 2 \][/tex]
### Step 4: Write the solution as an ordered pair.
The solution to the system of equations is:
[tex]\[ (x, y) = (6, 2) \][/tex]
Thus, the answer is [tex]\((6, 2)\)[/tex].
Given equations:
1. [tex]\( y = x - 4 \)[/tex]
2. [tex]\( 4x + y = 26 \)[/tex]
### Step 1: Substitute the expression for [tex]\( y \)[/tex] from the first equation into the second equation.
From the first equation, we can express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ y = x - 4 \][/tex]
Now, substitute [tex]\( y = x - 4 \)[/tex] into the second equation:
[tex]\[ 4x + (x - 4) = 26 \][/tex]
### Step 2: Simplify the equation and solve for [tex]\( x \)[/tex].
Combine like terms:
[tex]\[ 4x + x - 4 = 26 \][/tex]
[tex]\[ 5x - 4 = 26 \][/tex]
Add 4 to both sides of the equation:
[tex]\[ 5x = 30 \][/tex]
Divide both sides by 5:
[tex]\[ x = 6 \][/tex]
### Step 3: Solve for [tex]\( y \)[/tex] using the value of [tex]\( x \)[/tex].
Substitute [tex]\( x = 6 \)[/tex] back into the first equation:
[tex]\[ y = 6 - 4 \][/tex]
[tex]\[ y = 2 \][/tex]
### Step 4: Write the solution as an ordered pair.
The solution to the system of equations is:
[tex]\[ (x, y) = (6, 2) \][/tex]
Thus, the answer is [tex]\((6, 2)\)[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.